Pandangan Al-Qur'an Tentang Kurikulum - Varizki Syaf Putra; Charles Charles (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
One of the human efforts in shaping Muslims as human beings is by creating a situation of conducive educational interaction in Islamic education. One of the goals of Islamic education is the need for a curriculum. The curriculum is a set of arrangements and plans related to materials, the content of teaching taught to students, and the learning methods used as guidelines for organizing educational units in the realization of educational goals, especially Islamic education. The curriculum components include objectives, teaching materials, teaching methods, and assessment. The Islamic education curriculum must refer to the Qur’an and hadith as its basis. The Qur’an contains verses or the Word of Allah SWT that contains the curriculum, which is related to materials, the content provided to students in educational institutions, such as monotheism educational, worship, morals, health, social skills, and aesthetics. Thus, students who have faith, noble character and knowledge will be realized as well as the realization of quality Muslim human civilization.